Increasing Student Activity Through Game and Reward Methods in Grade IV Mathematics Content - Adhiba Anis Safitri; Fani Nur Anggita; Fariza Putri Nabila; Agung Setyawan (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This research aims to identify the factors that cause students to be less active in learning mathematics and to find out whether there is an increase in student involvement after implementing the game method accompanied by giving rewards in the form of praise or physical forms in mathematics subjects. The research was conducted in class IV at SDN Nyormanis 2 using the classroom action research method. This method was implemented through cycles 1 and cycle 2. In cycle 1 the researchers used the quiz game method which was carried out in groups and accompanied by rewards in the form of praise and applause. Meanwhile, in cycle 2 the researchers used the quiz game method but individually and accompanied by giving rewards in the form of snacks. Each cycle found an increase in student involvement in the learning process after giving rewards. The percentage of activeness in cycle I increased compared to the pre-cycle, then the percentage of activeness in cycle II increased compared to cycle I. The factor causing students to be inactive in learning was students' lack of motivation towards the learning process. Therefore, it can be concluded that the use of game methods with rewards is effective in increasing student involvement in mathematics subjects.